Corneal dendritic cells in diabetes mellitus: A narrative review - Liu, Fengyi; Liu, Chang; Lee, Isabelle Xin Yu; Lin, Molly Tzu Yu; Liu, Yu-Chi (Frontiers in Endocrinology, 2023)
Diabetes mellitus is a global public health problem with both macrovascular and microvascular complications, such as diabetic corneal neuropathy (DCN). Using in-vivo confocal microscopy, corneal nerve changes in DCN patients can be examined. Additionally, changes in the morphology and quantity of corneal dendritic cells (DCs) in diabetic corneas have also been observed. DCs are bone marrow-derived antigen-presenting cells that serve both immunological and non-immunological roles in human corneas. However, the role and pathogenesis of corneal DC in diabetic corneas have not been well understood. In this article, we provide a comprehensive review of both animal and clinical studies that report changes in DCs, including the DC density, maturation stages, as well as relationships between the corneal DCs, corneal nerves, and corneal epithelium, in diabetic corneas. We have also discussed the associations between the changes in corneal DCs and various clinical or imaging parameters, including age, corneal nerve status, and blood metabolic parameters. Such information would provide valuable insight into the development of diagnostic, preventive, and therapeutic strategies for DM-associated ocular surface complications.